Screening efficiency of the Mood and Feelings Questionnaire (MFQ) and Short Mood and Feelings Questionnaire (SMFQ) in Swedish help seeking outpatients - Jarbin, Håkan (PLoS One, 2020)
BACKGROUND: To evaluate screening efficiency and suggest cut-offs for parent and child Mood and Feelings Questionnaire (MFQ) and the short version (SMFQ) in unselected help seeking child- and adolescent psychiatric outpatients for subgroups of 6–12 versus 13–17 year olds and boys versus girls. METHOD: Eligible for inclusion were newly admitted outpatients age 6–17 years (n = 5908) in four Swedish child- and adolescent psychiatry clinics. They were prompted consecutively and n = 307 accepted a specific day for assessment until time slots randomly were filled. We prospectively validated the MFQ (33 items) and SMFQ (13 items) in patients (n = 186) using receiver operating characteristics against a reference test of Longitudinal Expert All Data DSM-IV depression based on a Kiddie-Schedule for Affective Disorders and Schizophrenia and 1.2 (sd .6) years of follow-up. RESULTS: A depressive disorder was confirmed in 59 (31.7%) patients ranging from 14.0% for girls 6–12 years to 53.3% for girls 13–17 years. SMFQ performed roughly equivalent to MFQ. Adolescent score on SMFQ discriminated fairly for boys with Area Under Curve .77 (95% confidence interval .59–.81) and good (.82, .69–.91) for girls and parent ratings for adolescent girls (.85, .73–.93), but not for boys. Depression in children below age 13 could not be discriminated by MFQ or SMFQ whether filled in by child and mostly also when filled in by parent. Favouring maximum kappa value, the optimal cut-off was for MFQ self-report girls ≥32 versus boys ≥11 and for SMFQ self-report girls ≥17 versus boys ≥ 6. Suggested clinical SMFQ cut-offs for girls were ≥12 and for boys ≥ 6. CONCLUSIONS: MFQ and SMFQ can, with gender-based cut-offs, be used for screening in clinical populations of adolescents but not in children. Parent MFQ and SMFQ can be used for adolescent girls but not boys. SMFQ is sufficient for screening.